TRENDS AND PROSPECTS OF THE DEVELOPMENT OF THE BANKING SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Turayev Sherkhon Momin ugli (The Conference Hub, 2025)
This paper analyzes the current development trends and strategic prospects of the banking system in the Republic of Uzbekistan. Particular attention is paid to the processes of digital transformation, privatization of state-owned banks, expansion of financial inclusion, and adoption of international financial standards. The study also outlines the main challenges, such as low financial literacy and cybersecurity risks, while emphasizing the potential of innovative technologies, green finance, and international cooperation in ensuring sustainable growth of the national banking sector.
Keywords: Uzbekistan, banking sector, digital transformation, financial reforms, banking liberalization, financial inclusion, sustainable development.